Post-Colonial Food Paradigms and Nutrition Governance in Indonesia - Isti Nuzulul Atiah; Siti Sofiaturrohmah (Dealings Foundation Institute, 2025)
The impact of colonial food paradigms on Indonesia’s nutrition policies and explore strategies for decolonizing perceptions of healthy food in East Nusa Tenggara (NTT) and Papua. Employing a comparative qualitative case study design, the research examines Indonesia alongside Vietnam and Peru, which have successfully integrated local foods into nutrition programs. Data collection involved secondary sources such as government reports, scientific articles, and policy documents, verified through data triangulation. The analysis utilized NVivo 12 Plus for thematic coding, focusing on actual conditions, challenges, and government responses related to food and nutrition governance. Results reveal that Indonesia’s persistent reliance on imported and industrialized foods, coupled with a diminished appreciation for indigenous foods like tubers, forest products, and local fish, hampers efforts to address malnutrition. Colonial legacies continue to influence public perception, overshadowing traditional foods' nutritional value. Conversely, Vietnam and Peru have demonstrated that embracing local food systems can significantly reduce stunting prevalence. The study concludes that adopting a decolonized, culturally sensitive approach to nutrition policies, which reintegrates local foods, is essential for improving nutritional outcomes and fostering food sovereignty in Indonesia. Such strategies can help reshape perceptions and enhance the resilience of local food systems against malnutrition.